Termination of rapid exhumation of the Jiaodong Peninsula during the Early Cretaceous: implications for explosive gold mineralization - Gao, Jianweng; Zhao, Keqiang; Duan, Zhuang; Fu, Yangang; Lin, Lujun; Wang, Zhenliang; Gong, Jingjing; Yang, Jianzhou; Li, Yong (Frontiers in Earth Science, 2025)
The proven gold deposits in the Jiaodong Peninsula, North China Craton, exceed 5,500 tons; these deposits are termed “Jiaodong type” or “Craton destruction type” owing to their unique geological features. Metallogenic chronology has dated the formation of these deposits at 120 ± 2 Ma. The development of such significant gold deposits in a relatively short period can be characterized as “explosive gold mineralization” and its driving factors are still under investigation. To clarify the geochemical characteristics, genesis and thermal history of a newly discovered quartz monzodiorite in the Tianqishan area, Shandong Province and their relationship with gold mineralization, the geochemistry of major and trace elements, zircon U–Pb isotope chronology, zircon Hf isotopes, and apatite fission track (AFT) thermochronology are analyzed. Our results show that the Tianqishan quartz monzodiorite, emplaced at ca. 119 Ma, is a metaluminous, high-K calc-alkaline rock, formed by mixing of mantle and crustal melts in a tectonic setting of North China Craton thinning. The AFT thermal history modeling results reveal four cooling events since the formation of the Tianqishan quartz monzodiorite and affirm two extensional stages in the Jiaodong Peninsula during the Early Cretaceous. The rapid exhumation of the crust of the Jiaodong Peninsula terminated at approximately ca. 120 ± 2 Ma, which may be due to the decoupling between crustal detachment and lithospheric mantle detachment in the Jiaodong Peninsula. Notably, the explosive mineralization of gold deposits aligns with the end of rapid exhumation in the Early Cretaceous, suggesting that decoupling between crustal and lithospheric mantle detachment is a plausible explanation for this phenomenon. This study provides critical new insights into the geodynamic processes governing Early Cretaceous lithospheric thinning and offers key constraints on the mechanisms driving explosive gold mineralization in the Jiaodong Peninsula.